2021
DOI: 10.1186/s12883-021-02095-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of thrombolysis for acute ischemic stroke with atrial fibrillation: a meta-analysis

Abstract: Background The efficacy and safety of intravenous thrombolysis (IVT) for acute ischemic stroke with atrial fibrillation (AF) is still controversial. Methods We conducted a meta-analysis of all relevant studies, retrieved through systematic search of PubMed, Embase, and Cochrane databases up to December 31, 2019. Modified Rankin Scale (mRS) scores of 0–1 at 90 days, mRS of 0–2 at 90 days, overall mortality, and incidence of symptomatic intracranial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 30 publications
4
28
1
Order By: Relevance
“…A meta-analysis by Lu et al about the safety and efficacy of IVT for AIS patients with AF and found worse outcomes in AIS patients with AF than those without AF. Authors also reported a higher incidence of sICH in AF patients than in non-AF patients (6.4% vs. 4.1%; p < 0.001), as well as in AF patients receiving IVT compared to AF patients not receiving IVT (5.7% vs. 1.6%; p < 0.001) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Lu et al about the safety and efficacy of IVT for AIS patients with AF and found worse outcomes in AIS patients with AF than those without AF. Authors also reported a higher incidence of sICH in AF patients than in non-AF patients (6.4% vs. 4.1%; p < 0.001), as well as in AF patients receiving IVT compared to AF patients not receiving IVT (5.7% vs. 1.6%; p < 0.001) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, intravenous thrombolysis (IVT) is less effective on both recanalization and clinical outcome but also increases the risk of intracranial hemorrhage (ICH) in patients with AF. The poor response to IVT could be partly explained by the pathophysiology of AF-related stroke, such as the gaps between patients with and without AF in terms of embolic size and components, collateral status, infarct core volume, and stroke progression [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“… 9 , 10 Despite receiving intravenous thrombolysis (IVT) treatment, patients with AF‐related acute ischemic stroke had poorer functional outcomes and higher hemorrhagic transformation risk. 11 , 12 In addition, compared with White patients with AF, Asian patients with AF had a higher incidence of stroke 13 , 14 and up to 2‐ to 4‐fold higher risk of intracranial bleeding. 15 , 16 , 17 , 18 …”
mentioning
confidence: 99%